Peran Guru Dalam Meningkatkan Minat Belajar Pendidikan Kewarganegaraan Menggunakan Media Flashcard Powerpoint Di SDN Berbah 2 Sleman - Chairiyah Ch (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This study aims to describe the role of teachers in increasing interest in learning civics education using powerpoint flashcard media for fourth grade students at SD Negeri Berbah 2 Sleman. The research method used is descriptive qualitative research. Data collection techniques in this study using observation, interview and documentation techniques. The validity test of the data in this study was carried out by increasing the persistence and triangulation techniques. The data analysis technique in this study used an interactive model from Miles and Huberman which consisted of several stages, namely data collection, data education, data presentation and conclusion drawing. The results of the study concluded that the role of teachers in fostering student interest in learning is very necessary so that civic education learning can be conveyed properly, teachers must carry out their functions as informators, facilitators, initiators, and evaluators, one of the teachers' creativity to increase interest in learning civic education is the use of flashcard media. power point. The use of powerpoint flashcard media can increase student interest in learning civic education.